2015
DOI: 10.1016/j.bbamcr.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nlrp3 inflammasome activation associated with lysosomal destabilization during coronary arteritis

Abstract: Inflammasomes play a critical role in the development of vascular diseases. However, the molecular mechanisms activating the inflammasome in endothelial cells and the relevance of this inflammasome activation is far from clear. Here, we investigated the mechanisms by which Nlrp3 inflammasome is activated to result in endothelial dysfunction during coronary arteritis by Lactobacillus casei (L. casei) cell wall fragments (LCWE) in a mouse model for Kawasaki disease. Endothelial dysfunction associated with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 50 publications
6
99
0
1
Order By: Relevance
“…In the endothelium, the functions of IL-1β include its pro-coagulant activity and the induction of adhesion molecules, which make it possible for the endothelium to trap leukocytes from the bloodstream (Bevilacqua et al 1985). Previous studies have emphasized the crucial role of IL-1β in the disruption of tight junctions leading to an increase in vascular permeability Chen et al 2015aChen et al , 2015bWang et al 2016). Inhibiting IL-1 activity has been shown to be effective in alleviating certain pathological conditions including type 2 diabetes and ischemic heart diseases (Abbate et al 2010;Larsen et al 2007;Van Tassell et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the endothelium, the functions of IL-1β include its pro-coagulant activity and the induction of adhesion molecules, which make it possible for the endothelium to trap leukocytes from the bloodstream (Bevilacqua et al 1985). Previous studies have emphasized the crucial role of IL-1β in the disruption of tight junctions leading to an increase in vascular permeability Chen et al 2015aChen et al , 2015bWang et al 2016). Inhibiting IL-1 activity has been shown to be effective in alleviating certain pathological conditions including type 2 diabetes and ischemic heart diseases (Abbate et al 2010;Larsen et al 2007;Van Tassell et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, palmitate-driven inflammasome activation in MVECs was prevented by treatment with a cathepsin B inhibitor , suggesting that lysosomal damage is capable of activating NLRP3 in endothelial cells. Furthermore, lysosomal membrane stabilizers also prevented NLRP3 inflammasome activation in a mouse model of coronary arteritis (Chen et al 2015a). Our present results with the lysosomal destabilizer Leu-Leu-OMe are in line with these earlier findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that bacteria activate the inflammasome via cathepsins [62-64]. For instance, it has been previously shown that infection of endothelial cells with Lactobacillus casei results in increased lysosomal permeability and a release of cathepsin B into the cytoplasm, finally mediating stimulation of the Nlrp3 inflammasome and arteritis [64].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been previously shown that infection of endothelial cells with Lactobacillus casei results in increased lysosomal permeability and a release of cathepsin B into the cytoplasm, finally mediating stimulation of the Nlrp3 inflammasome and arteritis [64]. Interestingly, free fatty acids such as palmitate also triggered a cathepsin B-mediated activation of the inflammasome [65] and it remains to be determined whether treatment with S. aureus α-toxin also mediates an intracellular release of free fatty acids contributing to increased lysosomal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Using established mouse models of coronary arteritis, recent studies have implicated NLRP3 inflammasome as a major intracellular molecular machinery able to switch on the inflammatory responses that contribute to the development of endothelial dysfunctions leading to atherosclerotic acceleration [100, Tomita, 1993 #125,101,102]. Such activation of the endothelial NLPR inflammasome is due to lysosome membrane permeabilization and cathepsin B release and can be suppressed by lysosome stabilization agents [103]. Thus, the Ad-induced inhibition of NLRP3 inflammasome activation, as recently documented [104] may represent an original and pivotal crosstalk mechanism to mitigate endothelial dysfunctions due to metabolic derangements.…”
Section: Endothelial Dysfunction and Metaflammationmentioning
confidence: 99%